2005
DOI: 10.1051/0004-6361:20052933
|View full text |Cite
|
Sign up to set email alerts
|

Helium settling and mass loss in magnetic Ap stars

Abstract: The chemical stratification is likely to play a predominant role in the excitation mechanism of high order modes in rapidly oscillating Ap stars. In this paper we discuss some processes (convection, He settling, mass loss and turbulent mixing) which may strongly affect the chemical composition of Ap stars. We discuss their interplay with a dipolar magnetic field in both magnetic polar and equatorial regions, where the magnetic lines are respectively mainly radially and horizontally oriented. We also present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 52 publications
2
28
0
Order By: Relevance
“…In single stars for which rotation cannot be slowed by tidal forces, strong magnetic fields may be the only process which sufficiently reduces rotation to allow chemical separation. Although it has to our knowledge never been shown that magnetic fields can completely eliminate convection, their topologies can induce horizontally dependent convection and abundance profiles (Babel & Michaud 1991), in addition to anisotropic mass loss and/or accretion (Théado et al 2005). If mass loss is in fact anisotropic, then strong mass loss rates, as suggested for young PMS stars by Boehm & Catala 1995, may be present only where field lines are vertical, and thus be compatible with anisotropic surface anomalies.…”
Section: General Discussion and Conclusionmentioning
confidence: 97%
“…In single stars for which rotation cannot be slowed by tidal forces, strong magnetic fields may be the only process which sufficiently reduces rotation to allow chemical separation. Although it has to our knowledge never been shown that magnetic fields can completely eliminate convection, their topologies can induce horizontally dependent convection and abundance profiles (Babel & Michaud 1991), in addition to anisotropic mass loss and/or accretion (Théado et al 2005). If mass loss is in fact anisotropic, then strong mass loss rates, as suggested for young PMS stars by Boehm & Catala 1995, may be present only where field lines are vertical, and thus be compatible with anisotropic surface anomalies.…”
Section: General Discussion and Conclusionmentioning
confidence: 97%
“…The diffusion of He in stellar atmospheres with well-mixed winds (including H) has been studied in more detail by Vauclair et al (1991), Krticka & Kubát (2004) and Théado et al (2005); all groups confirm that without a mixed wind from the star, that He should diffuse downwards until quite low relative abundance is reached. However, we know of no published predictions of how low the He abundance should drop before an equilibrium distribution is achieved.…”
Section: Abundant Light Elements: He Omentioning
confidence: 90%
“…This hypothesis has been tested with reasonable success through nonadiabatic calculations (Cunha 2002). Moreover, microscopic diffusion is also supposed to have a significant impact on the excitation process (Théado et al 2005).…”
Section: Introductionmentioning
confidence: 89%